INTERPRETATION OF THE SUBSURFACE STRUCTURE OF A GEOTHERMAL AREA X MANIFESTATION OF MAGNETIC DATA USING THE POLYGON METHOD TALWANI - MARISKA MARDIKAWATI MAING (NIM : 90213015), CLAUDIA
Magnetic methods is one of the methods in the field of geophysical surveys are often used in the early stages of exploration. The purpose of the magnetic survey is to investigate areas experiencing anomalous magnetic fields caused by the presence of magnetic materials contained in the rocks below the earth's surface. This method is based on the difference in the level of magnetic rock induced by Earth's magnetic field. In this study discussed about the spread of the magnetic anomaly in a region "X" which has a geothermal potential seen from the map contours and shapes anomalies below the surface of the area "X". In the data interpretation stage anomalous object modelling was performed using Matlab programming using the polygon method Talwani the forward modeling process. The initial phase is made using a contour map making software surfer. To create a contour map is used as the data 322 in the form of position coordinates of the observations in this case the observation point (X and Y) and anomalous magnetic fields in each of those points. Having obtained the contour map the spread of anomalous magnetic fields at the survey site characterized by the color difference for each value anomalous in which the magnetic field is obtained that the magnetic anomalies in the area "X" range between -1400 nT to 2000 nT. Having obtained the distribution anomalous value of the magnetic field, then the next step is to choose one slice will be analyzed to obtain a picture of anomalous shapes along the slice. Selection slice chosen based on differences in magnetic field anomaly is significant in this case of the negative and positive, but it is also based on manifestations in the field. Based on the slice that has been chosen, it will obtain the coordinates of the observation point values (X and Y) and anomalous magnetic field by using digitize that as many as 83 data. From the existing data will be further processed to make modelling using Matlab using the polygon method Talwani the forward modeling process. Process forward modeling done by trial and error value of the distance (X) and depth (Z) of anomalous objects that are in the slice. After this process several times, it was found that predicted anomalous objects that are under the surface of the area along the slice has five sides with coordinate points X and Z as follows [2346,034; 756,446], [3264,55; 98,502], [843,876;1218,446], [5338;1586], [3164,032; 832,687]meter with suseptibility value of -0.0123 ÃƒÂ— 103 (SI) which is included in the diamagnetic materials.